2017
DOI: 10.1016/j.proci.2016.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Computational characterization of ignition regimes in a syngas/air mixture with temperature fluctuations

Abstract: Auto-ignition characteristics of compositionally homogeneous reactant mixtures in the presence of thermal non-uniformities and turbulent velocity fluctuations were computationally investigated. The main objectives were to quantify the observed ignition characteristics and numerically validate the theory of the turbulent ignition regime diagram recently proposed by Im et al. [H.G. Im, P. Pal, M.S. Wooldridge, A.B. Mansfield, Combustion Science and Technology, 2015] that provides a framework to predict ignition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The ignition regimes were classified into three categories: (1) weak ignition with the dominant mode of deflagration, (2) reaction-dominant strong, and (3) mixing-dominant strong with the dominant mode of spontaneous ignition. A recent DNS study has been conducted to verify the ignition regime diagram using syngas [66]. The results were consistent with the predictions by the ignition regime diagram.…”
Section: Introductionsupporting
confidence: 73%
“…The ignition regimes were classified into three categories: (1) weak ignition with the dominant mode of deflagration, (2) reaction-dominant strong, and (3) mixing-dominant strong with the dominant mode of spontaneous ignition. A recent DNS study has been conducted to verify the ignition regime diagram using syngas [66]. The results were consistent with the predictions by the ignition regime diagram.…”
Section: Introductionsupporting
confidence: 73%
“…In single-fuel (SF) constant-volume conditions, there is a body of literature available that scrutinize the importance of ignition and subsequent combustion modes, where effects of temperature [23,[27][28][29][30][31][32][33][34][35][36][37][38][39] , and/or composition [33][34][35]39,40] , and/or velocity [28,31,35,36,38] fluctuations are taken into account. For instance, Pal et al [28,38] proposed regime diagrams which specify different modes of combustion with velocity and temperature fluctuations. More recently, Luong et al [39] studied the role of temperature and composition fluctuations based on a theoretical analysis for dimethyl ether/air mixtures and validated it against two-dimensional (2d) direct numerical simulations (DNS).…”
Section: Introductionmentioning
confidence: 99%
“…As 3D DNS involving accurate models for chemical, diffusion and thermodynamic processes are still not practical for systematic studies, the present work is mainly focused on 2D configurations, as done also for instance in [20, 21, 23, 28–30]. Yu et al [31] compared 2D and 3D DNS of auto-ignition of a lean H 2 /air mixture, and concluded that 3D turbulence results in faster heat transfer rate than 2D.…”
Section: Introductionmentioning
confidence: 99%